2007
DOI: 10.1007/s11581-007-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of FeS2 for lithium batteries

Abstract: Nanocrystalline FeS 2 cathode material of lithium cell was synthesized from cheap materials of FeSO 4 , Na 2 S 2 O 3 , and sulfur by a hydrothermal process. The scanning electron microscopy analysis showed the obtained material was nano-sized, about 500 nm. The X-ray powder diffraction analysis showed that the synthetic FeS 2 material had two phases of the crystalline structure, pyrite and marcasite. The phase of marcasite seems to have no negative effect on the electrochemical performance of the material. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…From Table 1, it can also be observed that two sulphurcontaining chemicals have always been preferred as the S sources to synthesize iron pyrite. One is elemental sulphur and the other is Na 2 S 2 O 3 or Na 2 S. Wu et al, 28 Feng et al, 29 Zhang et al 30 and Xia et al 38 used Na 2 S 2 O 3 and elemental sulphur as the S precursors to synthesize iron pyrite at hydrothermal conditions. The iron pyrite samples they obtained contained irregular particles or aggregation of polyhedrons.…”
Section: Hydrothermal Synthesismentioning
confidence: 99%
“…From Table 1, it can also be observed that two sulphurcontaining chemicals have always been preferred as the S sources to synthesize iron pyrite. One is elemental sulphur and the other is Na 2 S 2 O 3 or Na 2 S. Wu et al, 28 Feng et al, 29 Zhang et al 30 and Xia et al 38 used Na 2 S 2 O 3 and elemental sulphur as the S precursors to synthesize iron pyrite at hydrothermal conditions. The iron pyrite samples they obtained contained irregular particles or aggregation of polyhedrons.…”
Section: Hydrothermal Synthesismentioning
confidence: 99%
“…Iron disulfide (FeS 2 ) is an attractive anode material for lithium ion batteries because of its interesting characteristics such as high theoretic capacity (890 mAh g -1 ), low environmental impact and affordable cost [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. However, the capacities of FeS 2 electrodes often reduce very quickly during charge-discharge cycling, especially at high current densities.…”
Section: Introductionmentioning
confidence: 99%
“…As a narrow-bandgap semiconductor with a direct band gap of 0.95 eV, pyrite (FeS 2 ) has attracted special attention in the scientific and industrial fields due to their unique optical, magnetic and electrochemical properties. For example, FeS 2 can be adapted to photoelectrochemical and photovoltaic solar cells (PECS), as a cathode material for lithium batteries, and as an anode depolarizer for hydrogen production [3][4][5]. Particularly, FeS 2 is a promising solar energy material owing to its environmental compatibility and its very high light absorption coefficient [6].…”
Section: Introductionmentioning
confidence: 99%